Unlocking Potentials of Microwaves for Food Safety and Quality - Tang, Juming (Journal of food science, 2015)
Microwave is an effective means to deliver energy to food through polymeric package materials, offering potential for developing short‐time in‐package sterilization and pasteurization processes. The complex physics related to microwave propagation and microwave heating require special attention to the design of process systems and development of thermal processes in compliance with regulatory requirements for food safety. This article describes the basic microwave properties relevant to heating uniformity and system design, and provides a historical overview on the development of microwave‐assisted thermal sterilization (MATS) and pasteurization systems in research laboratories and used in food plants. It presents recent activities on the development of 915 MHz single‐mode MATS technology, the procedures leading to regulatory acceptance, and sensory results of the processed products. The article discusses needs for further efforts to bridge remaining knowledge gaps and facilitate transfer of academic research to industrial implementation.